Pandangan Yusuf Qardawi dalam Kitab Daurul Qiyam Wal Akhlaq Fil Iqtishadil Islami Mengenai Etika Produksi, Konsumsi dan Distribusi dalam Upaya Membangun Kesadaran Bisnis Beretika - Ghofur, Abdul; Samsuri, Ali (Al-Muzdahir : Jurnal Ekonomi Syariah, 2024)
The term Islamic economics has existed since the religion of Islam emerged in the world. Yusuf alQardhawi described Islamic Economics as an economic system rooted in religious principles. According to him, this is a system inspired and regulated by Allah SWT, with goals and laws originating from His teachings. All economic activities, such as production, distribution, consumption, and international trade, are directed by divine principles and aim to gain God's approval. In an era of globalization that tends to ignore morals and ethics, Yusuf al-Qardhawi emphasizes the importance of Economic Ethics, which he considers to be the guardian of economic sustainability. This research uses a qualitative approach to explore and explain qualities and social aspects that cannot be measured quantitatively. The scientific method used is library research, which relies on data and information from various sources in the literature. From a production perspective, Islamic Economics encourages everyone to work diligently and compete to find work, because this is considered an obligation and honor, as well as the right of every individual. In the consumption aspect, the wise use of wealth is emphasized, remembering that ownership of wealth is not the main goal, but rather a means to enjoy God's gifts. In distribution, the main principles are freedom and justice. Freedom in this case rejects oppression that hampers the lives of ordinary people and controls their sources of sustenance. Justice is defined as appropriate placement in the position that it should be.